(untitled) (Annals of Medical Research, 2021)
Aim: The aim of the present study is to investigate the factors which influence vaccination status against seasonal influenza and pneumococcus in patients with sickle cell anemia which is known to be the most common hereditary hematologic disease worldwide.Materials and Methods: This prospective, cross-sectional study was conducted with the volunteer patients above 18 years who were admitted to Hematology Clinic of Baskent University Adana Research and Training Center due to sickle cell anemia during 01 December – 31 December 2018.Results: Of 38 patients, 22 (57.9%) were females. Ratio of vaccination against pneumococcus was found to be higher among the patients who had vaccination cards (p0.05). Ratio of vaccination against pneumococcus and influenza was found to be higher among the patients who were coming for regular controls and the difference was statistically significant (p0.05). The reason for not getting vaccinated was detected to be “forgetting vaccination” (37.5%), “not believing the necessity of vaccination” (25%) and “not being recommended by health authorities” (25%).Conclusion: It was concluded that vaccination rates could be increased through using vaccination cards, inviting the patients for regular controls and health authorities’ recommending vaccination.